Kadar SGOT dan SGPT pada Penderita Demam Berdarah Dengue - Cahyaningrum Trisnowati (Jaringan Laboratorium Medis, 2019)
Dengue hemorrhagic fever (DHF) is still one of the health problems in the world because its prevalence tends to increase and its spread is wider. Liver dysfunction is a result of dengue infection which often appears in the form of hepatomegaly and mild-to-moderate elevations in the enzyme aminotransferase (SGOT SGPT). Aminotransferase enzymes tend to be higher along with the severity of the disease. The purpose of this study was to determine the levels of SGOT and SGPT in patients with DHF who were treated at Harapan Magelang Hospital in January 2020 until March 2020. This research is descriptive. The number of samples in this study were 83 patients who were treated at Harapan Magelang Hospital. Sampling was done by consecutive sampling. The results of the study resulted in an increase in SGOT by 84.7% and an increase in SGPT by 51.8%. Most of the increase in SGOT is mild-moderate, increasing 1-3 x from the normal value of 53% n = 44/83 and increasing 3-10x from the normal value of 26.5% n = 22/83 while the SGPT is mostly still within normal limits 48.5% n = 40/83. The average SGOT level obtained was 129.5 U / l and the average SGPT level was 87.7 U / L. The conclusion was that SGOT levels increased more mildly 1-3 x than normal values and SGPT levels were still within normal limits in patients with dengue fever.